The king of Kong : [videorecording (DVD)] : a fistful of quarters - Gordon, Seth; Wiebe, Steve; Mitchell, Billy, 1965-; Day, Walter (New Line Home Entertainment, 2008)
Unprecedented rivalry rocks the electronic world to its core. Join novice gamer Steve Wiebe on his quest to destroy the top score of gaming legend Billy Mitchell, the uncontested champion of the Donkey Kong world for over 20 years. Only one can truly claim the title King of Kong.